2020
DOI: 10.1039/c9me00069k
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration of de novo inorganic complexes for chemical discovery and machine learning

Abstract: Enumerated, de novo transition metal complexes have unique spin state properties and accelerate machine learning model training.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 112 publications
0
48
0
Order By: Relevance
“…We employ two subsets of data, as curated in prior work 60 from five prior studies [33][34][35]107,115 that originally corresponded to a total of 2,828 mononuclear octahedral transition-metal complexes in equilibrium geometries obtained with gas-phase density functional theory (DFT). In comparison to the prior curation 60 (i.e., where the sets were referred to as MD1 and OHLDB), we refined the data further by de-duplicating structures with identical molecular graph, charge, and spin state across the two sets.…”
Section: Computational Details 4a Data Sets and Calculation Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…We employ two subsets of data, as curated in prior work 60 from five prior studies [33][34][35]107,115 that originally corresponded to a total of 2,828 mononuclear octahedral transition-metal complexes in equilibrium geometries obtained with gas-phase density functional theory (DFT). In comparison to the prior curation 60 (i.e., where the sets were referred to as MD1 and OHLDB), we refined the data further by de-duplicating structures with identical molecular graph, charge, and spin state across the two sets.…”
Section: Computational Details 4a Data Sets and Calculation Detailsmentioning
confidence: 99%
“…Details of all complexes are provided in the ESI. As in the original studies [33][34][35]107,115 For all DFT geometry optimizations carried out in the original work, TeraChem 116 , as automated by molSimplify 117,118 and molSimplify automatic design (mAD) 107 , was employed.…”
Section: Computational Details 4a Data Sets and Calculation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table S13: electron conguration vector for MP dataset. structure properties (quantum-mechanically-derived properties), [12][13][14] crystallographic parameters, 15,16 or material synthesis parameters. 17,18 If prediction models for nanomaterials are excluded from the scope of discussion, no models for inorganic compounds were developed to predict endpoints signicant in a regulatory perspective except one which predicts inorganic toxicity of substances toward rats.…”
Section: Introductionmentioning
confidence: 99%
“…TMCs are often used as bio-inspired homogeneous catalysts which account for over 15% of all industrial catalytic processes and enable key catalytic transformations such as for pharmaceuticals, fine chemicals, and energy applications [22,23,24,25,26,27,28,29]. Recent studies have revealed the promise of data-driven quantum chemical methods to understand structure-function relations in TMCs [30,31,32,33,34,35]. Availability of structure-property data from QM calculations and/or experiments is central to the success of data-driven chemical approaches.…”
Section: Introductionmentioning
confidence: 99%